Prevalence of stunting among under-five children in refugee and internally displaced communities: a systematic review and meta-analysis - Choudhary, Priyanka; Padhi, Bijaya K.; Mital, Amit Kumar; Gandhi, Aravind P.; Mishra, Sanjeeb Kumar; Suri, Neha; Baral, Sudhansu Sekhar; Satapathy, Prakasini; Shamim, Muhammad Aaqib; Thangavelu, Lakshmi; Rustagi, Sarvesh; Sah, Ranjit; et al. (Frontiers in Public Health, 2023)
Background A pooled estimate of stunting prevalence in refugee and internally displaced under-five children can help quantify the problem and focus on the nutritional needs of these marginalised groups. We aimed to assess the pooled prevalence of stunting in refugees and internally displaced under-five children from different parts of the globe. Methods In this systematic review and meta-analysis, seven databases (Cochrane, EBSCOHost, EMBASE, ProQuest, PubMed, Scopus and Web of Science) along with 'preprint servers' were searched systematically from the earliest available date to 14 February 2023. Refugee and internally displaced (IDP) under-five children were included, and study quality was assessed using "National Heart, Lung, and Blood Institute (NHLBI)" tools. Results A total of 776 abstracts (PubMed=208, Scopus=192, Cochrane=1, Web of Science=27, Embase=8, EBSCOHost=123, ProQuest=5, Google Scholar=209, Preprints=3) were retrieved, duplicates removed and screened, among which 30 studies were found eligible for qualitative and quantitative synthesis. The pooled prevalence of stunting was 26% (95% confidence interval [CI]: 21-31). Heterogeneity was high (I2 = 99%, p<0.01). Subgroup analysis on the type of study subjects revealed the pooled stunting prevalence of 37% (95% CI: 23-53) in IDP and 22% (95% CI: 18-28) among refugee children. Based on geographical distribution, the stunting was 32% (95% CI: 24-40) in the African region, 34% (95% CI: 24-46) in the South-East Asian region and 14% (95% CI: 11-19) in Eastern Mediterranean region. Conclusion The stunting rate is more in the internally displaced than the refugee population, and more in the South-East Asian and African regions. Our recommendation is to conduct further research to evaluate the determinants of undernutrition among under-five children of refugees and internally displaced populations from different regions so that international organisations and responsible stakeholders of that region can take effective remedial actions.